(untitled) (Perner’s Contacts, 2007)
In transport sector EU implements common transport policy. There are a number of important reasons. Functional and reliable transport is a condition of creation of single market with unlimited movement of goods and persons. Transport sector affects many other spheres: regional development, environment, landscaping, energy consumption and other. Reliable function of transport sector is a prerequisite to economical connection of member states without barriers. It requires creation of common rules for each member state and harmonization of prescripts (technical, safety, working and others).